2019
DOI: 10.1021/acs.est.9b01835
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Paraffins in Car Tires Recycled to Rubber Granulates and Playground Tiles

Abstract: Chlorinated paraffins (CPs) are used in various products to improve their physicochemical characteristics. Due to recycling, CPs may end up in “new” recycled products. In this study we investigated CPs present in end-of-life car tires that are recycled to rubber granulates used on artificial soccer fields, and playground tiles. The ∑CP(C10-C30) concentrations ranged from 1.5 to 67 μg/g in car tires, 13–67 μg/g in rubber granulates, and 16–74 μg/g in playground tiles. MCCPs were the dominant CP group with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 28 publications
3
49
0
1
Order By: Relevance
“…Svanberg and Linden (1979) pointed out that CPF were being used as PCB replacements in many applications such as secondary plasticizers, oil additives and flame retardants following restrictions on the use of PCB. More recently, used car tires have been identified as an important source of chlorinated paraffins to the environment (Brandsma et al, 2019). It seems plausible that both these sources have contributed to the CPF concentrations determined in these samples.…”
Section: Contaminant Levelsmentioning
confidence: 94%
“…Svanberg and Linden (1979) pointed out that CPF were being used as PCB replacements in many applications such as secondary plasticizers, oil additives and flame retardants following restrictions on the use of PCB. More recently, used car tires have been identified as an important source of chlorinated paraffins to the environment (Brandsma et al, 2019). It seems plausible that both these sources have contributed to the CPF concentrations determined in these samples.…”
Section: Contaminant Levelsmentioning
confidence: 94%
“…Chlorinated Paraffins (CPs) are a group of substances that are applied in various products as plasticizers, coolants and flame retardants because of their chemical and thermal stability 1 . CPs are high-volume production chemicals (> 1 million metric tonnes yr −1 ) and are regularly released into the environment during production, transportation, and recycling processes and through leaching and volatilization from landfills 2 4 . Short-chain chlorinated paraffins (SCCPs; C 10 -C 13 ) are found to be persistent, bioaccumulative and toxic (PBT) to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In past years, especially in urban areas, the presence of sport and recreational facilities made up of recycled crumb rubber is increasing. This material, formed by end-of-life tires contains high concentrations of PAHs, heavy metals, plasticizers, and hazardous organic compounds [18][19][20][21]. Some studies have demonstrated the transfer of toxic compounds from the crumb rubber to the runoff water and air [22,23], although most of them are simulated studies at laboratory scale [24,25].…”
Section: Introductionmentioning
confidence: 99%